In Vitro Activities of ME1036 (CP5609), a Novel Parenteral Carbapenem, against Methicillin-Resistant Staphylococci - Kurazono, Mizuyo (American Society for Microbiology, 2004)
ME1036, formerly CP5609, is a novel parenteral carbapenem with a 7-acylated imidazo[5,1-b]thiazole-2-yl group directly attached to the carbapenem moiety of the C-2 position. The present study evaluated the in vitro activities of ME1036 against clinical isolates of gram-positive and gram-negative bacteria. ME1036 displayed broad activity against aerobic gram-positive and gram-negative bacteria. Unlike other marketed β-lactam antibiotics, ME1036 maintained excellent activity against multiple-drug-resistant gram-positive bacteria, such as methicillin-resistant staphylococci and penicillin-resistant Streptococcus pneumoniae (PRSP). The MICs of this compound at which 90% of isolates were inhibited were 2 μg/ml for methicillin-resistant Staphylococcus aureus (MRSA), 2 μg/ml for methicillin-resistant coagulase-negative staphylococci, and 0.031 μg/ml for PRSP. In time-kill studies with six strains of MRSA, ME1036 at four times the MIC caused a time-dependent decrease in the numbers of viable MRSA cells. The activity of ME1036 against MRSA is related to its high affinity for penicillin-binding protein 2a, for which the 50% inhibitory concentration of ME1036 was approximately 300-fold lower than that of imipenem. In conclusion, ME1036 demonstrated a broad antibacterial spectrum and high levels of activity in vitro against staphylococci, including β-lactam-resistant strains.